A produção tecnológica de software e o mercado brasileiro - Ota, Rafael Kouhei [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Digitization and the impacts of technology have increasingly deepened in society and in the world economy. Software, being a necessary element for any device related to information technology, plays a central role in this development scenario, as does the startup ecosystem and innovation. The objective of this work is to analyze the technological production of software and its market, and directly related topics, such as startups, public policies and investments, bringing the national situation, compared to world leaders and other comparable countries. A documental research was carried out from different sources to carry out the diagnosis and forecasts and perspectives were presented for the subjects addressed. In the end, it was possible to understand some of the problems and difficulties faced by Brazil, in the light of other developing countries that have also achieved relative success through different paths. Emerging themes in the Software market were also discussed, such as “Software as Service”.

A digitalização e o impactos da tecnologia têm se aprofundado cada vez mais na sociedade e na economia mundial. O software, sendo um elemento necessário para qualquer dispositivo relacionado a tecnologia da informação, têm papel central nesse cenário de desenvolvimento, assim como o ecossistema de startups e a inovação. O objetivo deste trabalho é analisar a produção tecnológica de software e seu mercado, e temas diretamente relacionados, como as startups, políticas públicas e investimentos, trazendo a conjuntura nacional, em comparação com os líderes mundiais e outros países comparáveis. Foi realizada uma pesquisa documental de diferentes fontes para realizar o diagnóstico e apresentadas previsões e perspectivas para os assuntos abordados. Ao final, foi possível entender alguns dos problemas e dificuldades enfrentados pelo Brasil, à luz de outros países em desenvolvimento que também obtiveram relativo sucesso através de caminhos diversos. Também foram discutidos temas emergentes no mercado de Software, como o “Software as Service”.
The technological production of software and the brazilian market
Keywords: Software; Startups; Innovation; Information technology; Inovação; Tecnologia da informação; Inovações tecnológicas